Pengenalan dan Bimbingan Teknis Penggunaan Alat-Alat Ukur Keteknikan di SMK Negeri 2 Kendari - Aminur; La Hasanudin; Sudia, Budiman; Sisworo, Raden Rinova; Endriatno, Nanang; Yurnidasyah, Citra (Indonesian Journal of Community Services, 2022)
Technological advances in measuring instruments provide convenience in carrying out the work of measuring an object. But on the other hand, these advances require skilled operators so that they can be applied to the object being measured. The purpose of this service activity is to increase the knowledge of teachers and students in recognizing various measuring tools to increase their competence in the use of measuring tools. The method of implementing the activity uses an approach to theoretical exposure, direct demonstration and practice, discussions, and questions and answers that are directly related to measuring instruments including solar power meters, viscometers, micrometers, thermometers, tachometers, torques, welding gauges, dial indicators, and anemometers. The results achieved from the implementation of this community service activity, teachers and students gain knowledge of various types of measuring instruments and how to apply them to various objects being measured.